(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
Da. Employment of strong acid, high acid concentration and high temperature produced darker coloured chitosan whereas milder treatments gave lighter coloured chitosan. Key words: Chitosan, Absidia sp. dr, degree of deacetylation, molecular weight